TaRECQ4 contributes to maintain both homologous and homoeologous recombination during wheat meiosis - Bazile, Jeanne; Nadaud, Isabelle; Lasserre-Zuber, Pauline; Kitt, Jonathan; De Oliveira, Romain; Choulet, Frédéric; Sourdille, Pierre (Frontiers in Plant Science, 2024)
Meiotic recombination (or crossover, CO) is essential for gamete fertility as well as for alleles and genes reshuffling that is at the heart of plant breeding. However, CO remains a limited event, which strongly hampers the rapid production of original and improved cultivars. RecQ4 is a gene encoding a helicase protein that, when mutated, contributes to improve recombination rate in all species where it has been evaluated so far. In this study, we developed wheat (Triticum aestivum L.) triple mutant (TM) for the three homoeologous copies of TaRecQ4 as well as mutants for two copies and heterozygous for the last one (Htz-A, Htz-B, Htz-D). Phenotypic observation revealed a significant reduction of fertility and pollen viability in TM and Htz-B plants compared to wild type plants suggesting major defects during meiosis. Cytogenetic analyses of these plants showed that complete absence of TaRecQ4 as observed in TM plants, leads to chromosome fragmentation during the pachytene stage, resulting in problems in the segregation of chromosomes during meiosis. Htz-A and Htz-D mutants had an almost normal meiotic progression indicating that both TaRecQ4-A and TaRecQ4-D copies are functional and that there is no dosage effect for TaRecQ4 in bread wheat. On the contrary, the TaRecQ4-B copy seems knocked-out, probably because of a SNP leading to a Threonine>Alanine change at position 539 (T539A) of the protein, that occurs in the crucial helicase ATP bind/DEAD/ResIII domain which unwinds nucleic acids. Occurrence of numerous multivalents in TM plants suggests that TaRecQ4 could also play a role in the control of homoeologous recombination. These findings provide a foundation for further molecular investigations into wheat meiosis regulation to fully understand the underlying mechanisms of how TaRecQ4 affects chiasma formation, as well as to identify ways to mitigate these defects and enhance both homologous and homoeologous recombination efficiency in wheat.